Окремі аспекти безпеки життєдіяльності гравців американської футбольної ліги - Задорожний, Г. С. (ХНУРЕ, 2019)
The result of this work has had an unprecedented impact on the activities of the National Football League in ensuring the safety of players. The League was forced to admit the validity of the collective suit of former football players, and took measures to increase the level of security of the game.